Integrative Islamic Counseling for the Elderly: A Ghazalian-Informed Psychospiritual Framework in Indonesia - Ragwan Albaar; Amriana Amriana; M. Yusuf; Abrohul Isnaini (Islamic Guidance and Counseling Journal, 2026)
In Indonesia, culturally grounded gerontological counseling frameworks rooted in Islamic intellectual traditions remain relatively underexamined despite growing scholarly attention to spirituality and aging. This study examines counseling practices for elderly individuals within Islamic institutional settings and interprets these practices through Al-Ghazali’s moral psychology to develop a Ghazalian-informed psychospiritual framework for elderly well-being. A qualitative multi-site interpretive case study was conducted across two Islamic elderly care institutions in East Java, Indonesia, involving 23 participants, including elderly residents, caregivers, and institutional staff. Data were collected through observations, interviews, field notes, and institutional documents, and analyzed using thematic analysis with iterative coding and cross-site comparison. The findings indicate that counseling practices within both institutions support emotional adaptation, spiritual reflection, moral guidance, and communal connectedness among elderly participants. These practices are not structured as formal clinical psychotherapy but are embedded within devotional routines and collective religious environments. Based on these empirical patterns, the study interprets the findings through a Ghazalian perspective and proposes a psychospiritual framework comprising interrelated domains of spiritual meaning-making, affective regulation, moral cultivation, and communal engagement. By situating these findings within Islamic moral anthropology, this study contributes a culturally grounded perspective to discussions on spirituality, aging, and Islamic counseling while recognizing the complementary role of spiritual care alongside professional mental health services.